How To Match The Universality Of The Convention On The Law Of The Sea And The Sovereignty Of Countries In The Field Of The Settlement Of Maritime Disputes (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Maritime Disputes are a type of international disputes that is subject to the rules of public international law, Maritime extensions are the core of the topic of maritime disputes between different countries, even if their intensity changes according to the region under dispute and its importance for the parties to the conflict, Perhaps the most frequent of these disputes are those related to various activities and practices in the territorial waters or the exclusive economic zone and continental shelf, and they are old and new, since the conflict is related to issues directly related to sovereignty  in its broadest sense in relation to the territorial waters of coastal states, or it is related  to the sovereign rights  in the economic zone or the continental shelf.In view of the multiplicity and diversity of the seriousness and complexity of maritime disputes, successive Law of the Sea Conferences have been striving to organize all matters relating to the seas.Perhaps the most important of these conference on the Law of the Sea, which resulted after several long and arduous negotiations, The United Nations Convention on the Law of the Sea, which is the basis of the new international law of the sea, as it represents a tremendous achievement in organizing all issues related  to the sea, perhaps the most important of these issues is the settlement of maritime disputes of all kinds, taking into account the sovereignty and freedom of states in a way that contributes to achieving universality of application of the convention, although it prevented reservations absolutely.